A phase 1 study of the BCL2-targeted deoxyribonucleic acid inhibitor (DNAi) PNT2258 in patients with advanced solid tumors - Tolcher, Anthony W.; Rodrigueza, Wendi V.; Rasco, Drew W.; Patnaik, Amita; Papadopoulos, Kyriakos P.; Amaya, Alex; Moore, Timothy D.; Gaylor, Shari K.; Bisgaier, Charles L.; Sooch, Mina P.; Woolliscroft, Michael J.; Messmann, Richard A. (Cancer chemotherapy and pharmacology, 2014)
Purpose Maximum tolerated dose, safety, pharmacokinetics, and pharmacodynamics were assessed in this phase 1 study of PNT2258, a BCL-2-targeted liposomal formulation of a 24-base DNA oligonucleotide called PNT100. Methods Patients with malignant solid tumors were assigned sequentially to one of ten dose-escalation cohorts of PNT2258 at 1, 2, 4, 8, 16, 32, 64, 85, 113, and 150 mg/m 2 administered intravenously on days 1 through 5 of each 21-day cycle. Pharmacokinetics were determined on days 1 and 5 of the first cycle. Lymphocyte and platelets concentrations were measured for evidence of BCL2-targeted effect. CT scans were used to identify radiologic evidence of anti-tumor effect. Results Twenty-two subjects received PNT2258, and the maximum tolerated dose for PNT2258 was not reached. Doses at or above 32 mg/m 2 resulted in exposure to PNT2258 above the exposure level required for anti-tumor activity in preclinical xenograft testing of 22,377 ng h/ml (PK analysis 2012 ). Fatigue was the most commonly reported adverse event. Dose-limiting toxicity, manifesting as a transient increase in aspartate aminotransferase, occurred at 150 mg/m 2 , the highest dose tested. Four subjects, two each with diagnosis of non-small-cell lung cancer and sarcoma, treated at doses of 64 mg/m 2 or higher, remained on study for 5–8 cycles. Conclusions PNT2258 was safe and well tolerated at the doses tested up to 150 mg/m 2 . Exposure to PNT2258 resulted in clinically manageable decreases in lymphocyte and platelet concentrations.